Synthesis and Crystal Structure of Dy(H2O)9(1,4-dimethylbenzene)2Cl4.H3O - Luo, Hui; Zhu, Li-Cheng (Asian Journal of Chemistry, 2015)
One-pot solvothermal reaction of DyCl3·6H2O with 1,4-dimethylbenzene and water generates Dy(H2O)9(1,4-dimethylbenzene)2Cl4·H3O that is characterized by single-crystal X-ray diffraction. The compound crystallizes in monoclinic, space group P21/m with a = 7.8378(10), b = 25.103(3), c = 7.9068(10) Å, b = 119.3850(10), V = 1355.5(3) Å3, C16H41Cl4DyO10, Mr = 697.79, Dc = 1.710 g/cm3, μ(MoKa) = 3.194 mm-1, F(000) = 702, Z = 2, the final R = 0.0503 and wR = 0.1323 for 2157 observed reflections (I > 2s(I)). The 2-D supramolecular layer is built up from the compound by hydrogen bonds.